LEASE FINANCING: A NEW DUAL APPROACH - Cristina-Aurora, BUNEA-BONTAS (Strategii Manageriale, 2013)
Leasing is an important additional financing technique used by many companies, enabling them to use property, plant and equipment without making large initial cash outlays. It also provides flexibility, allowing entities to address obsolescence risks. Under current accounting rules, when referring to the operating leasing in particular, there is a lack of comparability between the financial position and operating results of companies that buy assets and the financial position and operating results of those that lease similar assets. This has led critics to assert that the current accounting does not portray the economics of lease arrangements. In response to this criticism, the IASB and FASB have developed a new approach to lease accounting that would require a lessee to recognise assets and liabilities for the rights and obligations created by leases, this providing greater transparency and comparability for financial statements users. On the other hand, the proposals will affect almost every company and the impact of the proposed changes may be significant, as recognising additional assets and liabilities and finance expense will affect key performance ratios and, consequently, the ability to satisfy debt covenants.